Assessment of biosafety training and practices in biomedical laboratories in Kinshasa, Democratic Republic of the Congo - Diane Sare Gamani; Gertrude Mongila Matimada; Lydie Hamunaki Masika; Placide Ngandu Cyanga; Tacite Kpanya Mazoba; Jérémie Masidi Muwonga (Orapuh Journal)
Introduction